2014
DOI: 10.3390/ijms15033519
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel-Loaded Chitosan Microspheres as a Lung Targeted Drug Delivery System: In Vitro and in Vivo Evaluation

Abstract: The aim of this study was to prepare docetaxel-loaded chitosan microspheres and to evaluate their in vitro and in vivo characteristics. Glutaraldehyde crosslinked microspheres were prepared using a water-in-oil emulsification method, and characterized in terms of the morphological examination, particle size distribution, encapsulation ratio, drug-loading coefficient and in vitro release. Pharmacokinetics and biodistribution studies were used to evaluate that microspheres have more advantage than the convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…These microspheres are obtained from spray-drying techniques, and the results of this study are also supported by other researchers. 61,62 Both drug-distribution schemes (ie, with SPP and conventional approaches) indicate that the organ/tissue is exposed to the drug to a greater extent if the Re (drug exposure) value is >1. The lungtargeting efficacy (Te) of the SPP formulation and the conventional formulation are shown in Table 4.…”
Section: In Vitro and Release Kineticsmentioning
confidence: 99%
“…These microspheres are obtained from spray-drying techniques, and the results of this study are also supported by other researchers. 61,62 Both drug-distribution schemes (ie, with SPP and conventional approaches) indicate that the organ/tissue is exposed to the drug to a greater extent if the Re (drug exposure) value is >1. The lungtargeting efficacy (Te) of the SPP formulation and the conventional formulation are shown in Table 4.…”
Section: In Vitro and Release Kineticsmentioning
confidence: 99%
“…Nanospheric particles as drug delivery systems are gaining increasing interest in the biomedical field. Nanospheres and microspheres are also found to be efficient drug delivery systems for intravenous administration because of their comparatively long bloodstream circulation (Hire and Derle, 2014;Wang et al, 2014). It was expected that when the drugs are released after internalization of micelle, by cleavage, they act as pro-drugs and enhance solubility of hydrophobic drugs, reduce drug toxicity, increase bioavailability, specificity, and systematic release of drugs, and prolong the drug action (Moghimi et al, 1993;Croy and Kwon, 2006;Dadwal, 2014).…”
Section: Polymeric Micellesmentioning
confidence: 97%
“…These results indicated that the microspheres could deliver SRI predominantly to lung tissue after i.v. administration, which is preferable for the treatment of lung cancer, and the reduction of side effects as well (Madan et al, 2013;Wang et al, 2014).…”
Section: Lung Targeting Performancementioning
confidence: 99%